HUBUNGAN TINGKAT KECEMASAN DENGAN TEKANAN DARAH PADA REMAJA DI SMAN 1 NGRAYUN PONOROGO - Intan Aprillia Melani; Nurul Sri Wahyuni; Saiful Nurhidayat; Siti Munawaroh; Yayuk Dwi Rahayu (Universitas Muhammadiyah Ponorogo, 2023)
Anxiety for adolescents can occur when adolescents are easily threatened or have low self-confidence. Adolescents who experience anxiety have the potential to experience changes in blood pressure due to unstable feelings. This study aims to determine the relationship between anxiety levels and blood pressure in adolescents at SMAN 1 Ngrayun Ponorogo.The method in this study is cross sectional correlation with an observational approach. The sample used was 73 class XII students at SMAN 1 Ngrayun obtained through simple random sampling method. Primary data were obtained by measuring blood pressure using a sphygmomanometer and the HARS questionnaire. The data that has been collected is then analyzed using the Spearman Rank Test correlation.The results showed that respondents who did not experience anxiety were 39 students (53.4%), mild anxiety were 23 students (31.5%), moderate anxiety was 5 students (6.8%), and severe anxiety was 6 students. (8.2%). Furthermore, respondents who had normal blood pressure scores were 47 students (64.4%), hypotension were 17 students (23.3%) and pre-hypertensive were 9 students (12.3%). Based on the results of the statistical analysis using the Spearman rank test, a p-value of 0.004 was obtained where the value was smaller than 0.01, so it was stated that H1 was accepted, there was a relationship between anxiety levels and blood pressure in adolescents at SMAN 1 Ngrayun Ponorogo.This research is expected to increase knowledge about hypertension such as providing regular education so that efforts can be made to reduce the risk of hypertension and control feelings of anxiety that may be faced.